Effect of divergent angle and water flowrate on mean bubble size in venturi-type generator: An experimental and computational approach - Nadumaran, N.; Erny Afiza, Alias; M. H., Hamidi; Nasrul Hadi, Johari (Faculty Mechanical Engineering, UMP, 2025)
Venturi nozzles, valued for their simple design and flexibility, are widely used to generate microbubbles (MB) via hydrodynamic cavitation, particularly in water treatment and agriculture. MB efficiency depends on bubble size, which is influenced by the Venturi geometry and flow parameters, such as divergent angle and water flow rate. However, the relationship between these factors and bubble size remains underexplored, especially through combined experimental and simulation approaches. This study addresses that gap by combining experimental visualization and computational fluid dynamics to assess the impact of divergent angle and water flow rate on MB generation. Three Venturi nozzles with divergent angles of 8°, 10°, and 12°, and flow rates of 13 L/min, 33 L/min, and 66 L/min were tested. Bubble size was measured using high-speed imaging and analyzed in MATLAB. Simulations were performed using ANSYS FLUENT with a coupled Eulerian–Lagrangian model and a Population Balance Model, enabling the detailed prediction of bubble size. Experimental and simulation results showed a relative error of less than 5%, confirming the reliability of simulations. Increasing the divergent angle and flow rate decreased the MB distribution, yielding smaller bubbles. The Venturi 3 (12° divergent angle) produced the smallest bubbles, measured experimentally at 519 µm and in simulations at 505 µm, at a flow rate of 66 L/min. The strong agreement between experimental and simulation results, with a maximum error of 4%, was supported by velocity profile analysis, which revealed the highest velocity (14.09 m/s) in Venturi 3, resulting in the formation of the smallest bubbles. These findings not only validate the effectiveness of the simulations in predicting bubble size but also offer valuable insights for optimising venturi designs.